The Continued Relevance of Global Citizenship Education: Addressing Global Challenges Through Learning - Agoi, Rosie (Advances in Social Sciences Research Journal, 2025)
In an era marked by rising nationalism and shifting attitudes toward globalization, Global Citizenship Education (GCED) remains a critical framework for fostering inclusive, responsible, and globally engaged individuals. While enthusiasm for globalization was once widespread, current trends indicate a retreat toward nationalistic policies, raising concerns about global cooperation, equity, and shared responsibility. This paper argues for the continued importance and relevance of GCED in addressing pressing global challenges such as climate change, migration, technological transformation, and socio-economic inequalities. Despite its significance, implementing GCED faces multiple obstacles. This study examines these challenges through the case of Uganda, where issues such as inadequate resources, weak infrastructure, and misalignment with national policies hinder the effective adoption of GCED. The Ugandan example illustrates broader systemic barriers that many countries face when integrating GCED into their educational frameworks. To enhance the implementation of GCED, this paper proposes targeted strategies, including curriculum reforms, teacher training programs, stronger public-private partnerships, and robust monitoring and evaluation mechanisms. By adopting these approaches, countries like Uganda can more effectively integrate GCED into their national education systems, ensuring that learners acquire the skills and values needed to navigate an interconnected world. This study contributes to the ongoing discourse on education’s role in global engagement and provides practical recommendations for policymakers seeking to sustain the relevance of GCED amid shifting geopolitical landscapes.